MODES OF WORK IN ENGLISH LANGUAGE EDUCATION WITH GIFTED CHILDREN - Khamidova Gulnoza Shakirovna (Bright Mind Publishing, 2025)
This article examines the idea of giftedness and reveals unconventional approaches to working with gifted kids.
Keywords: kinds of instruction, types of teachings, giftedness, extracurricular program, skills.